Efektivitas Model SMEERI (Self Management Education for Pregnancy Risk) Melalui Video Edukasi dalam Meningkatkan Pengetahuan dan Keterampilan Kader Tentang Deteksi Dini Tanda Bahaya Kehamilan - Nisma; Nurul Hidayah; Nadia Rahmawati; Nurul Jamil (Sci-tech Journal, 2025)
Pregnant women are vulnerable to various risks during pregnancy, so it is important for women to care about the condition of the fetus and themselves during this period. A self management education approach with the SMEERI model is needed to conduct early detection of pregnancy danger signs. This study aims to analyse the effectiveness of the SMEERI (Self Management Education for Pregnancy Risk) model through educational videos in improving the knowledge and skills of cadres on early detection of pregnancy danger signs. The study used a Quasi Experimental design with a pre-test and post-test approach in one group without a control group. The total respondents in this study were 15 posyandu cadres in the Tambelan Sampit Health Centre Working Area. The results showed that the Smeeri model through educational videos had a significant impact in improving knowledge and skills in early detection of pregnancy danger signs in health cadres. This study suggests that the development of the Smeeri programme can be applied in digital products or platforms that are easily accessible to the community.